A methodology to investigate the readiness of cost data inputs for the estimation of total cost of a new flexible pavement construction in Malaysia - Bidi, Nor Khalisah; Ayob, Mohd Fairullazi; Abdul Rashid, Khairuddin (PIBEC Secretariat D-03A-3, PLAZA PARAGON, POINT 2,JALAN MEDAN PUSAT BANDAR 5, SEKSYEN 9, 43650 BANDAR BARU BANGI, SELANGOR, MALAYSIA, 2017)
Life Cycle Cost (LCC) estimation of flexible pavement consists of three phases; i.e. data inputs, conversion, and outputs. Based on the literature study, most of the LCC practitioners only emphasised to conversion rather than the quality of data inputs of flexible pavement. However, a reliable and comprehensive LCC estimation of flexible pavement only can be attained if more focuses are given on the quality of data inputs. The objective of the paper is to present a methodology proposed for the study to investigate the readiness of cost data as inputs for the estimation of the total cost of a new flexible pavement construction throughout an anticipated study life. This paper reports part of a two year of master research undertaken by the first author to investigate the readiness of cost data as inputs for the estimation of the total cost of a new flexible pavement construction in Malaysia. The methodology designed for the study is a qualitative research that comprises of literature review and two fieldwork approaches; i.e. face to face interview and focus group discussion. Comments and recommendations are needed in effort for further improvement of the methodology proposed for the study.